The Profound Effect of the Ring Size in the Electrocyclic Opening of Cyclobutene‐Fused Bicyclic Systems1. (5th December 2014) - Ralph, Michael J.; Harrowven, David C.; Gaulier, Steven; Ng, Sean; Booker‐Milburn, Kevin I.
Abstract Fused cyclobutenes, prepared by the photocycloaddition of propargyl alcohols to cyclic anhydride chromophores, undergo facile thermochemical ring opening to fused γ‐lactones. The size of the fused ring profoundly influences the temperature that is required to facilitate the ring opening (from 50 °C to 180 °C) and the nature of the product that is formed. Our studies provide new insights into the mechanistic course of these reactions and have been extended to facilitate the preparation of lactams fused to medium‐sized rings.